Websites for women's studies students: finding, evaluating, promoting. Issue 1 (16th January 2017) - Clink, Kellian
Abstract : Purpose: This paper aims to identify and review websites that contribute knowledge about and by women for scholars in women's studies. Design/methodology/approach: The authors scoured the internet for those sites with timely, authoritative research reports about and by women with a feminist viewpoint. Findings: There are many gems that provide statistical, theoretical and heuristic insights into the condition of women that may, unless promoted, not be discovered by students who need them. Research limitations/implications: New websites will be created and others described herein will evolve. Practical implications: The lived experiences of women are largely not covered by standard reference sources, and this requires the librarian to seek out and promote the freely available websites out there that help inform scholars about the experiences of half the world's population. Originality/value: There is not one place where the gender and women's studies librarian can go to find a comprehensive list of the freely available resources that can benefit the feminist scholar, and this paper brings together many of them in one place.